Histomorphometric and immunohistochemical assessment of RUNX2 and VEGF of Biogran™ and autogenous bone graft in human maxillary sinus bone augmentation: A prospective and randomized study - Pereira, Rodrigo dos Santos [UNESP]; Menezes, Juliana Dreyer [UNESP]; Bonardi, João Paulo [UNESP]; Griza, Geraldo Luiz [UNESP]; Okamoto, Roberta [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (Wiley, 2017)
Background: Few studies have been conducted to assess new bone formation using Biogran, a bioactive glass, in maxillary sinus bone augmentation through a prospective and randomized evaluation. Moreover, there are no studies that evaluate cellular behavior by immunohistochemical assessment for osteoblastic and vascular activity during bone repair. Purpose: The aim of this study is to compare new bone formation and cellular behavior with Biogran alone, a 1:1 combination of Biogran and autogenous bone graft, and autogenous bone graft alone in human maxillary sinuses. Materials and methods: Ten maxillary sinuses were grafted with Biogran (Group 1), 10 grafted with Biogran added to autogenous bone graft in a 1:1 ratio (Group 2), and 10 grafted with autogenous bone graft alone (Group 3). After 6 months of bone healing, samples were obtained concurrent to the dental implants' placement to be evaluated by histomorphometric and immunohistochemical assessment for RUNX2 and vascular endothelial growth factor (VEGF). Results: The amount of new bone formation in Group 1 was 42.0 ± 7.3% in the pristine bone region, 40.7 ± 14.0% in the intermediate region, and 45.6 ± 13.5% in apical region. In Group 2, for pristine bone, intermediate, and apical regions, new bone formation was 36.6 ± 12.9%, 33.2 ± 13.3%, and 45.8 ± 13.9%, respectively. Group 3 showed new bone formation of 37.3 ± 11.6%, 35.3 ± 14.7%, and 39.9 ± 15.8% in pristine bone, intermediate, and apical regions, respectively. The immunolabeling for RUNX2 showed low cellular activity in osteoblasts for all groups, and the VEGF assessment demonstrated moderate cellular activity in Groups 1 and 2; however, Group 3 presented with low activity in the pristine bone region, followed by moderate activity in the intermediate and apical region. Conclusion: This study demonstrates that Biogran and its combination with autogenous bone graft 1:1 are good bone substitutes due to their similarity to autogenous bone graft.
Keywords: bioactive glass; biomaterials; bone substitutes; maxillary sinus floor elevation